Una propuesta integral de evaluación en Ciencias - Rodríguez Barreiro, L. M.; Gutiérrez Múzquiz, F. A.; Molledo Cea, J. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
In the following study, we are going to deal with evaluation problems, one of the aspects in the curriculum that has undergone less changes in the last years. In order to do so, we will analyse critically the way it is done nowadays. Next, we will enunciate a series of force -ideas to propitiate the change in this field of activity. Finally, we will show the ethnographic evaluation pattern, the one we have chosen, going deeply into the methods and techniques for data -collecting more commonly used in this kind of research. Besides, we will try to explain those patterns with examples, mostly taken from our everyday practice with BUP students.